Insights into the mechanisms of triptolide nephrotoxicity through network pharmacology-based analysis and RNA-seq - Luo, Yue-Ming; Yang, Shu-Dong; Wen, Miao-Yu; Wang, Bing; Liu, Jia-Hui; Li, Si-Ting; Li, Yu-Yan; Cheng, Hong; Zhao, Li-Li; Li, Shun-Min; Jiang, Jian-Jun (Frontiers in Plant Science, 2023)
Triptolide (TPL) is a promising plant-derived compound for the therapy of multiple human diseases; however, its application was limited considering its toxicity. To explore the underlying molecular mechanism of TPL nephrotoxicity, a network pharmacology based approach was utilized to predict candidate targets related with TPL toxicity, followed by deep RNA-seq analysis to characterize the features of three transcriptional elements include protein coding genes (PCGs), long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) as well as their associations with nephrotoxicity in rats with TPL treatment. Our results suggested that c-Jun is a potential target and circadian rhythm signaling is involved in TPL induced renal toxicity.